Are Aortic Valve Reoperations after Primary Replacement with Stentless Heart Valve Prostheses More Demanding than after Stented Biological Prostheses? - Böning, Andreas; Niemann, Bernd; Ennker, Ina; Richter, Michael; Roth, Peter; Ennker, Jürgen (The Thoracic and Cardiovascular Surgeon, 2014)
Objective Reoperations after aortic valve replacement (AVR) with stentless valve prostheses are believed to be surgically more difficult than after stented prostheses.Methods Between January 1996 and December 2006, 1,340 of 3,785 patients with AVR in a single institution received a stentless valve prosthesis in aortic position (Medtronic Freestyle, Medtronic GmbH, Meerbusch, Germany). Reoperations after stentless AVR occurred in 27 patients (2.0%). Twenty-four of these patients were compared with another 24 patients having redo surgery after a primary stented bioprosthesis after carrying out propensity score matching.Results After matching, stentless valve redo patients had a similar preoperative risk profile regarding EuroSCORE (stentless 10 ± 3 points/stented 11 ± 3 points; p = 0.37), preoperative active endocarditis (stentless 37.5%/stented 16.7%; p = 0.081), and amount of concomitant procedures (stentless 37.5%/stented 16.7%; p = 0.222). Thirty-day mortality after reoperation was 20.8% (5 patients) in the stentless and 4.2% (1 patient) in the stented group (p = 0.081), and reintubation rate was 16.7% in the stentless and 0% in the stented group (p = 0.037). Aortic clamping time (stentless 90 ± 25 min/stented 86 ± 34 min; p = 0.208) and extracorporeal circulation time (stentless 151 ± 59 min/stented 132 ± 52 min; p = 0.55) were similar in both groups.Conclusion Our data do not show that the technical difficulty of reoperations after stentless AVR is higher than that of reoperations after stented AVR. The clinically visible, but not statistically significant, higher early mortality rate of our stentless group is mainly due to more active valve prosthesis endocarditis cases and a higher amount of concomitant procedures.
Keywords: reoperation; aortic valve replacement; biological aortic valve prosthesis; stentless aortic valve prosthesis; perioperative complications